Pterygodermatites cahirensis IN PALM CIVET CAT (Paradoxurus hermaphroditus): A CASE REPORT - S.T. Bino Sundar; Thirunagari Ramanujadas; K.T. Kavitha; Bhaskaran Ravi Latha; B. Nishanth; M. Palanivelrajan; K. Sridhar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The occurrence of the spirurid nematode, Pterygodermatites cahirensis in a Palm civet cat (Paradoxurus hermaphroditus) observed during necropsy is reported. The worms were found in the intestinal content. Male worms were small and slender compared to females. The worms had two rows of spines on the lateroventral sides along the whole length of the body. Males had short spicules. Females had uterus filled with developing ova. Eggs were thick-shelled with undifferentiated yolk mass.